Scholarly Responses to Political and Religious Challenges: A Comparative Study of Islamic Scholars during the Invasions of Ghazan Khan and Amir Timur - Thanachot Prahyadsap (LECTURES: Journal of Islamic and Education Studies, 2025)
This study aims to examine the responses of Islamic scholars during the invasions of Ghazan Khan in the 13th century and Amir Timur in the 15th century, focusing on how they navigated the political and religious challenges posed by these rulers. Using a comparative analytical approach, the research explores the reactions of scholars who collaborated with the Mongols, such as Qadi Ibrahim bin Ali, alongside those who opposed them, like Ibn Taymiyyah. The study also investigates responses during the Timurid invasions, focusing on scholars like Qadi Abdul Jabbar and Muhammad al-Hardi. The findings reveal that Islamic scholars displayed a range of responses, from collaboration to resistance, influenced by both political and religious factors. The research highlights the complex relationship between governance, religion, and survival during periods of conquest. This study contributes to a deeper understanding of the role of scholars in shaping religious discourse amid political and religious upheaval.